2019
DOI: 10.1002/cbdv.201900377
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Evaluation of Mannich Bases Derived from 1,2,4‐Triazole

Abstract: The series of novel Mannich bases were synthesized and evaluated for their in vitro antibacterial activity against Gram‐positive and Gram‐negative bacterial strains. The results showed that all compounds were less active than the drugs used as reference, but some of them had moderate potency against Staphylococcus epidermidis ATCC 12228 and Bacillus subtilis ATCC 6633. The presence of a phenyl ring in the position 4 of piperazine seems to be necessary for antibacterial activity in this class of compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Several studies show that a common compound that is carried out in the numerous fields of biology and medicine is a five-membered heterocyclic compound, and its nitrogen-containing structure with high activities against several pathogens like antifungal, antibacterial, antiviral, and others could be found in 1,2,4-triazoles Mannich bases 20 .…”
Section: Orginal Articlementioning
confidence: 99%
“…Several studies show that a common compound that is carried out in the numerous fields of biology and medicine is a five-membered heterocyclic compound, and its nitrogen-containing structure with high activities against several pathogens like antifungal, antibacterial, antiviral, and others could be found in 1,2,4-triazoles Mannich bases 20 .…”
Section: Orginal Articlementioning
confidence: 99%
“…Liu et al reported a novel substituted 3,5-diamine-1,2,4-triazole from isothiocynate and mono-substituted hydrazines and sodium hydrogen cyanamide (Scheme 6 ) [ 27 ].
Scheme 6 Novel substituted 3,5-diamine-1,2,4-triazole
…”
Section: Main Textmentioning
confidence: 99%
“…[48] Extensive literature reports have highlighted the potency of Mannich base-linked 1,2,4-triazole derivatives as antibacterial, [49][50][51] antifungal, [52,53] antitubercular, [54] anti-cancer agents. [55,56] As existing drugs on the market often face challenges such as drug resistance, undesirable toxic side effects, and incompatibility with other drugs, there is an urgent need for the synthesis of novel biologically active compounds. These new candidates should possess safety profiles, exhibit strong biological activity, have rapid action, and be non-toxic, thereby meeting the current medical demands.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, by selecting the appropriate amine reagent, the Mannich reaction can also contribute to enhancing the lipophilic properties of a drug [48] . Extensive literature reports have highlighted the potency of Mannich base‐linked 1,2,4‐triazole derivatives as antibacterial, [49–51] antifungal, [52,53] antitubercular, [54] anti‐cancer agents [55,56] . As existing drugs on the market often face challenges such as drug resistance, undesirable toxic side effects, and incompatibility with other drugs, there is an urgent need for the synthesis of novel biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%